Analisis Risiko Sistematis Saham Syariah Berdasarkan Sektor (Model Aplikasi GARCH) Pada Bursa Efek Indonesia (BEI) Periode Januari 2007- Desember 2016 - ROHIM, LUKMAN NUR (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this study is to investigate the relationship between macroeconomic factor and systemic risk sectoral based on Indonesia Stock Exchange. The study use monthly data of beta stock based on sharia compliant using Generalized AutoRegressive Conditional Heteroscedasticity (GARCH) model. The results showed that macroeconomic factors give diffrents effect to beta stock in diffrente sector, because of characteristics each sector respond differently to macroeconomics condition in Indonesia. Simultaneously, macroeconomic variables affect the systematic risk of stock. BI rate affects positively and significantly on consumer goods and infrastructure sectors. Exchange rate and Crude Price Oil (CPO) have significantly and positively effect to systemic risk all sector. Inflation have positively and significantly effect to systemic risk on agriculture, mining, infrastructure, and property. Economic crisis condition on 2008 negatively affect on all sector. Keywords : Systemic Risk, CAPM, Sharia-Compliant Stock, GARCH. Â